17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference) 2011
DOI: 10.2514/6.2011-2757
|View full text |Cite
|
Sign up to set email alerts
|

Hermite Methods for Aeroacoustics: Recent Progress

Abstract: We present recent developments on Hermite methods for aeroacoustic simulations including time-stepping methods, hybridization with discontinuous Galerkin methods for handling of boundary conditions and adaptive implementations. By scaling studies reported below we show that the features unique to Hermite methods have promise to enable efficient exploitation of modern petascale architectures. We also present preliminary computations of turbulent jet noise obtained with the current implementation of our compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Even for serial computations, we have shown that Hermite methods are more efficient than difference methods even in simple geometry for all but the least stringent error requirements. See, in particular, Figure 3 in Appelö et al 5…”
Section: Comparisons With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for serial computations, we have shown that Hermite methods are more efficient than difference methods even in simple geometry for all but the least stringent error requirements. See, in particular, Figure 3 in Appelö et al 5…”
Section: Comparisons With Other Methodsmentioning
confidence: 99%
“…This paper will report on recent progress on the development, analysis and application of a class of methods known as Hermite methods 8 which are arbitrarily high order accurate, and very suitable for parallel architectures. This work is a continuation of our research program [3][4][5]9 on Hermite methods and their application to jet noise.…”
Section: Introductionmentioning
confidence: 99%
“…This is advantageous for high order or multi-stage timestepping methods compared to finite difference methods, where neighboring data must be accessed each time derivatives are approximated. This structure has also been noted to be well-suited for parallel implementations on modern architectures [2,11]. Hermite schemes, which were initially introduced for Cartesian domains, have also been coupled with discontinuous Galerkin (DG) schemes for numerical simulations on complex geometries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hermite schemes, which were initially introduced for Cartesian domains, have also been coupled with discontinuous Galerkin (DG) schemes for numerical simulations on complex geometries [4]. They have also been applied to problems in aeroacoustics [2], electromagnetics [4], and fluid dynamics [16].…”
Section: Introductionmentioning
confidence: 99%
“…To enable geometric flexibility, Hermite methods have been combined with discontinuous Galerkin methods [5]. Adaptive variants of Hermite methods have been introduced by means of padaptivity in [4], and preliminary work on h-adaptivity has been presented in [2]. Variations of the method which do not require a dual grid have been introduced in [15], and a flux conservative Hermite method has been introduced in [8].…”
mentioning
confidence: 99%